KLASIFIKASI PENDIDIK PERSPEKTIF AL-QUR’AN (Analisis Tafsir Tematik) - munawaroh, mas'ulil (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Abstrak Rahmawati , Liyana. 2020. The Improvement Critical Thinking Skills and of economic Test Student Learning by Cooperative Learning Type Think Talk Write atten grade class high school patriot jombang. STAISAM pungging Mojokerto. Economics is always assumed difficulty by students. So that way, the teachers must be effective to choosethe approach of learning. One of learning that use is cooperatif type TTW. This research was held on the 1st semester of ten grade high school Patriot year 2019/2020 with number 32 students. This research use techniq to collect observation of test studentslearning. . The result of research show that students activity of learning process of cycle show inproving from first cycle, to focuson the teacher's explanations by 75%, 78% asking questions, active indiscussion 87.5%, and make summary 81.3% .the result of first cycle 1 is about68.59 with 69%, second cycle 87.5 with 100%. so, learning through cooperative learning type TTW with economic systems can improve the result of students learning ten grade class High School Patriot academic year 2019/2020. Keywords : Cooperative Learning type TTW , critical thinking activityand the result of students learning.